Developing competent leaders in Malaysian Higher Education: an interview with the vice-chancellor of Universiti Malaya, Y. Bhg. Datuk Rafiah Salim - Abdul Rahman, Shukran; Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
To compete with the best in the world, and hence be recognised as world class, universities must establish a strong academic reputation. University leaders must therefore ensure that t heir institutions uphold the academic tradition to “publish or perish” and pursue excellence in teaching, learning and research